Chemical and topographical analysis of the surface of dental implants - Muñante Cárdenas, Jose Luis (2012)
The aim of this study was to analyze the chemical composition and surface topography of commercially pure titanium implants, obtained from three trademarks frequently used in dentistry. There were nine titanium implants of the following systems: As Technology, Neodent and Sistema Nacional de Implantes. These materials were divided into three groups, with three implants in each group. Photoelectron Spectroscopy Excited by X-ray (XPS) was used to determine the chemical composition, while to characterize the surface topography we used Scanning Electron Microscopy (SEM). Titanium, carbon, silicon and oxygen were identified in all samples analyzed. Other contaminants were: silicon, aluminum, sulfur, lead, phosphorus, calcium, sodium and nitrogen. We identified impurities on the surface of all implants analyzed. We consider necessary to development more studies relating the presence and concentration of these elements with the osseointegration process.